Kanski's clinical ophthalmology: A systematic approach - Salmon, John F. (Elsevier, 2020)
The 9th Edition retains Dr. Kanski's highly effective format of succinct text and visually dynamic presentation, providing authoritative, focused guidance on the diagnosis and management of ophthalmic disorders. Extremely well organized and comprehensive in scope, this visually stunning book reflects the latest advances in the field, facilitating quick comprehension to enhance learning, aid exam preparation and guide clinical practice. As a general ophthalmic textbook, this is the gold standard.